Structure of the Complex between Plastocyanin and Cytochrome f from the Cyanobacterium Nostoc sp. PCC 7119 as Determined by Paramagnetic NMR - Irene Díaz‐Moreno; Antonio Díaz‐Quintana; Miguel Á. De la Rosa; Marcellus Ubbink (2005)
The complex between cytochrome f and plastocyanin from the cyanobacterium Nostoc has been characterized by NMR spectroscopy. The binding constant is 16 mm–1, and the lifetime of the complex is much less than 10 ms. Intermolecular pseudo-contact shifts observed for the plastocyanin amide nuclei, caused by the heme iron, as well as the chemical-shift perturbation data were used as the sole experimental restraints to determine the orientation of plastocyanin relative to cytochrome f with a precision of 1.3 Å. The data show that the hydrophobic patch surrounding tyrosine 1 in cytochrome f docks the hydrophobic patch of plastocyanin. Charge complementarities are found between the rims of the respective recognition sites of cytochrome f and plastocyanin. Significant differences in the relative orientation of both proteins are found between this complex and those previously reported for plants and Phormidium, indicating that electrostatic and hydrophobic interactions are balanced differently in these complexes. The complex between cytochrome f and plastocyanin from the cyanobacterium Nostoc has been characterized by NMR spectroscopy. The binding constant is 16 mm–1, and the lifetime of the complex is much less than 10 ms. Intermolecular pseudo-contact shifts observed for the plastocyanin amide nuclei, caused by the heme iron, as well as the chemical-shift perturbation data were used as the sole experimental restraints to determine the orientation of plastocyanin relative to cytochrome f with a precision of 1.3 Å. The data show that the hydrophobic patch surrounding tyrosine 1 in cytochrome f docks the hydrophobic patch of plastocyanin. Charge complementarities are found between the rims of the respective recognition sites of cytochrome f and plastocyanin. Significant differences in the relative orientation of both proteins are found between this complex and those previously reported for plants and Phormidium, indicating that electrostatic and hydrophobic interactions are balanced differently in these complexes. In oxygen-evolving photosynthetic organisms, light-driven ATP synthesis requires the participation of cytochrome b6f complex (1Blankenship R.E. Molecular Mechanisms of Photosynthesis. Blackwell Science Ltd., Oxford2002Crossref Scopus (855) Google Scholar, 2Allen J.F. Trends Plant Sci. 2004; 9: 130-137Abstract Full Text Full Text PDF PubMed Scopus (66) Google Scholar), which couples proton translocation across the thylakoid membrane to the electron transport between PSI 1The abbreviations used are: PSI, photosystem I; PSII, photosystem II; Cf, water-soluble fragment of cytochrome f; HSQC, heteronuclear single-quantum coherence; Pc, plastocyanin; PCd, cadmium plastocyanin; PCS, pseudo-contact shifts; r.m.s.d., root mean square deviation; WT, wild type. and PSII (3Kallas T. Bryant D.A. The Molecular Biology of Cyanobacteria. Kluwer Academic Publishers Group, Dordrecht, Netherlands1994: 259-317Crossref Google Scholar). In the cytochrome b6f complex, cytochrome f (Cf) transfers electrons from the Rieske iron sulfur cluster to a soluble metalloprotein that acts as the electron donor for the P700 cofactor of PSI. The Cf subunit consists of a ∼28-kDa N-terminal soluble part anchored to the membrane by a C-terminal helix (4Gray J.C. Photosynth. Res. 1992; 34: 359-374Crossref PubMed Scopus (75) Google Scholar). It represents an atypical c-type cytochrome because of both its β-sheet secondary structure and the unusual heme axial coordination (5Martinez S.E. Huang D. Szczepaniak A. Cramer W.A. Smith J.L. Structure. 1994; 2: 95-105Abstract Full Text Full Text PDF PubMed Scopus (261) Google Scholar). The long axis of the soluble part is tilted relative to the membrane normal, and the heme is oriented appropriately for approach of the Rieske protein from the membrane side and of plastocyanin (Pc) from the luminal side (6Kurisu G. Zhang H.M. Smith J.L. Cramer W.A. Science. 2003; 302: 1009-1014Crossref PubMed Scopus (598) Google Scholar, 7Stroebel D. Choquet Y. Popot J.L. Picot D. Nature. 2003; 426: 413-418Crossref PubMed Scopus (509) Google Scholar). Pc is the most ubiquitous electron carrier between Cf and P700 (8Sandmann G. Reck H. Kessler E. Böger P. Arch. Microbiol. 1983; 134: 23-27Crossref Scopus (80) Google Scholar). It is a type I cupredoxin (9Adman E.T. Adv. Protein Chem. 1991; 42: 145-197Crossref PubMed Google Scholar) that consists of an anti-parallel β-sandwich structure with a single copper atom (10Coleman P.M. Guss J.M. Sugimura Y. Yoshizaki F.Y. Freeman H.C. J. Mol. Biol. 1978; 211: 617-632Google Scholar, 11Sykes A.G. Chem. Soc. Rev. 1985; 14: 283-321Crossref Google Scholar, 12Redinbo M.R. Yeates T.O. Merchant S. J. Bioenerg. Biomembr. 1994; 26: 49-66Crossref PubMed Scopus (137) Google Scholar) that is coordinated by two nitrogen atoms and two sulfur atoms from highly conserved residues. In addition to its physiological relevance, the electron transfer reaction between Cf and Pc represents an excellent case to study the transient nature of protein interactions in electron transfer chains (13Bendall D.S. Bendall D.S. Protein Electron Transfer. BIOS Scientific Publishers Ltd., Oxford1996: 43-64Google Scholar). The lifetime of this kind of complexes is on the order of 1 ms or less. Due to the large amount of functional data available, this reaction has become a very useful model to test theoretical approaches for the prediction of structures of protein-protein complexes (14Pearson D.C. Gross E.L. David E.S. Biophys. J. 1996; 71: 64-76Abstract Full Text PDF PubMed Scopus (45) Google Scholar, 15Soriano G.M. Ponamarev M.V. Tae G.S. Cramer W.A. Biochemistry. 1996; 35: 14590-14598Crossref PubMed Scopus (72) Google Scholar, 16Soriano G.M. Cramer W.A. Krishtalik L.I. Biophys. J. 1996; 73: 3265-3276Abstract Full Text PDF Scopus (33) Google Scholar, 17Ullmann G.M. Knapp E.W. Kostic N.M. J. Am. Chem. Soc. 1997; 119: 42-52Crossref Scopus (108) Google Scholar, 18Pearson D.C. Gross E.L. Biophys. J. 1998; 75: 2698-2711Abstract Full Text Full Text PDF PubMed Scopus (58) Google Scholar, 19De Rienzo F. Gabdouline R.R. Menziani M.C. Benedetti P.G. Wade R.C. Biophys. J. 2001; 81: 3090-3104Abstract Full Text Full Text PDF PubMed Scopus (80) Google Scholar, 20Gross E.L. Pearson D.C. Biophys. J. 2003; 85: 2055-2068Abstract Full Text Full Text PDF PubMed Scopus (39) Google Scholar). In plants this reaction shows fast kinetics at 100 mm ionic strength (>108 m–1 s–1) despite both its modest binding constant (∼7 mm–1) under these conditions and the small difference in redox potential (20 mV) between donor and acceptor (21Kannt A. Young S. Bendall D.S. Biochim. Biophys. Acta. 1996; 1277: 115-126Crossref PubMed Scopus (118) Google Scholar, 22Hope A.B. Biochim. Biophys. Acta. 2000; 1456: 5-26Crossref PubMed Scopus (193) Google Scholar). The mechanism of this electron transfer reaction has been studied with several techniques (22Hope A.B. Biochim. Biophys. Acta. 2000; 1456: 5-26Crossref PubMed Scopus (193) Google Scholar). Such studies support the importance of electrostatic interactions involving the acidic patches ("site 2") on Pc and the basic residues of Cf for binding under in vitro conditions (23Soriano G.M. Ponamarev M.V. Piskorowski R.A. Cramer W.A. Biochemistry. 1998; 37: 15120-15128Crossref PubMed Scopus (56) Google Scholar, 24Gong X.S. Wen J.Q. Fisher N.E. Young S. Howe C.J. Bendall D.S. Gray J.C. Eur. J. Biochem. 2000; 267: 3461-3468Crossref PubMed Scopus (39) Google Scholar, 25Lee B.H. Hibino T. Takabe T. Weisbeek P.J. Takabe T. J. Biochem. 1995; 117: 1209-1217Crossref PubMed Scopus (1) Google Scholar, 26Illerhaus J. Altschmied L. Reichert J. Zak E. Herrmann R.G. Haehnel W. J. Biol. Chem. 2000; 275: 17590-17595Abstract Full Text Full Text PDF PubMed Scopus (51) Google Scholar) and the essential role of specific residues in the hydrophobic patches of both Cf (27Gong X.S. Went J.Q. Gray J.C. Eur. J. Biochem. 2000; 267: 1732-1742Crossref PubMed Scopus (20) Google Scholar) and Pc (26Illerhaus J. Altschmied L. Reichert J. Zak E. Herrmann R.G. Haehnel W. J. Biol. Chem. 2000; 275: 17590-17595Abstract Full Text Full Text PDF PubMed Scopus (51) Google Scholar). Notably, the relevance of the electrostatic interactions could not be confirmed in vivo (15Soriano G.M. Ponamarev M.V. Tae G.S. Cramer W.A. Biochemistry. 1996; 35: 14590-14598Crossref PubMed Scopus (72) Google Scholar). In the system from Phormidium laminosum, the only cyanobacterium for which the kinetics of the reduction reaction have been analyzed so far, the electrostatic effects appear to be weaker and less optimized compared with plants (28Schlarb-Ridley B.G. Bendall D.S. Howe C.J. Biochemistry. 2002; 41: 3279-3285Crossref PubMed Scopus (60) Google Scholar, 29Hart S.E. Schlarb-Ridley B. Delon C. Bendall D.S. Howe C. Biochemistry. 2003; 42: 4829-4836Crossref PubMed Scopus (33) Google Scholar). The solution structures of two Pc-Cf complexes have been obtained by dissecting the diamagnetic and paramagnetic contributions to the chemical-shift perturbations of Pc resonances upon Cf binding. The first one (PDB entry 2PCF) corresponds to the complex between spinach Pc and turnip Cf (30Ubbink M. Ejdebäck M. Karlsson B.G. Bendall D.S. Structure. 1998; 6: 323-335Abstract Full Text Full Text PDF PubMed Scopus (259) Google Scholar), and the second corresponds to the proteins from P. laminosum (31Crowley P.B. Otting G. Schlarb-Ridley B.G. Canters G.W. Ubbink M. J. Am. Chem. Soc. 2001; 123: 10444-10453Crossref PubMed Scopus (101) Google Scholar). Both structures show modest interface areas (600–850 Å2 per protein). Moreover, in both cases the hydrophobic patch of Pc ("site 1") lies near Tyr-1 of Cf, thus providing an appropriate environment for efficient electron transfer toward the copper atom through the exposed copper-coordinating His residue. In addition to this, chemical-shift perturbation data have been reported for several heterologous plant and cyanobacterial systems (32Crowley P.B. Vintonenko N. Bullerjahn G.S. Ubbink M. Biochemistry. 2002; 41: 15698-15705Crossref PubMed Scopus (30) Google Scholar, 33Crowley P.B. Ubbink M. Acc. Chem. Res. 2003; 36: 723-730Crossref PubMed Scopus (123) Google Scholar, 34Crowley P.B. Hunter D.M. Sato K. McFarlane W. Dennison C. Biochem. J. 2004; 378: 45-51Crossref PubMed Scopus (22) Google Scholar). Despite their similarities, significant differences are found between the cyanobacterial and the plant complexes. In Phormidium, Pc binds Cf in a "head-on" conformation in which the hydrophobic patch accounts for the whole recognition interface in Pc, contrary to the "side-on" interface that also involves the acidic patches, which is found in the plant complex. Both kinds of complexes have been predicted in theoretical studies using the co-ordinates from plant proteins (15Soriano G.M. Ponamarev M.V. Tae G.S. Cramer W.A. Biochemistry. 1996; 35: 14590-14598Crossref PubMed Scopus (72) Google Scholar, 16Soriano G.M. Cramer W.A. Krishtalik L.I. Biophys. J. 1996; 73: 3265-3276Abstract Full Text PDF Scopus (33) Google Scholar, 17Ullmann G.M. Knapp E.W. Kostic N.M. J. Am. Chem. Soc. 1997; 119: 42-52Crossref Scopus (108) Google Scholar). The ionic strength dependences of the structures suggest that in the plant complex electrostatics play a dominant role, whereas in Phormidium complex formation is governed by the hydrophobic effect. It is known that Phormidium is a thermophilic organism (35Castenholtz R.W. Schweiz. Z. Hydrol. 1970; 32: 538-551Google Scholar). A higher ambient temperature could influence the balance between electrostatic forces and hydrophobic effects, making this complex unusual and different from that in other cyanobacteria. Hence, it is unknown if differences between the reported plant and Phormidium complexes are applicable to all cyanobacteria. Here, the structure of the complex between Pc and Cf from another cyanobacterium, Nostoc (formerly Anabaena), has been determined. Interestingly, the results herein presented are consistent with a single conformation in the transient complex between Pc and Cf that resembles the characteristic side-on binding mode present in plants yet has an interface similar to that found in the Phormidium complex. Protein Preparation—Uniformly (99%) 15N-labeled Nostoc sp. PCC 7119 Pc was produced in Escherichia coli JM109 transformed with pEAP-WT (36Molina-Heredia F.P. Hervás M. Navarro J.A. De la Rosa M.A. Biochem. Biophys. Res. Commun. 1998; 243: 302-306Crossref PubMed Scopus (40) Google Scholar). The culture conditions and purification methods will be published elsewhere (64Díaz-Moreno I. Díaz-Quintana A. De la Rosa M.A. Crowley P.B. Ubbink M. Biochemistry. 2005; 44: 3176-3183Crossref PubMed Scopus (34) Google Scholar). Cadmium substitution of the copper in plastocyanin was performed as published (37Ubbink M. Lian L.Y. Modi S. Evans P.A. Bendall D.S. Eur. J. Biochem. 1996; 242: 132-147Crossref PubMed Scopus (42) Google Scholar) except that a PD-10 column (Amersham Biosciences) pre-equilibrated with a solution of 50 mm HEPES, pH 7.0, containing 1 mm CdCl2 was used instead of a Sephadex G25 gel filtration column. The soluble part of Nostoc sp. PCC 7119 Cf was produced in E. coli DH5α transformed with both pEC86, containing the c-type cytochrome maturation cassette (38Schulz H. Fabianeck R.A. Pellicioli E.C. Hennecke H. Thöny-Meyer L. Proc. Natl. Acad. Sci. U. S. A. 1999; 96: 6462-6467Crossref PubMed Scopus (103) Google Scholar), and an expression vector for Cf, pEAF-WT, obtained by insertion of a chimeric petA gene in pBluescript II (Stratagene). This chimeric gene coded for a fusion protein with Cf truncated at the C terminus (at position 253) and the signal peptide of cytochrome c6 (36Molina-Heredia F.P. Hervás M. Navarro J.A. De la Rosa M.A. Biochem. Biophys. Res. Commun. 1998; 243: 302-306Crossref PubMed Scopus (40) Google Scholar). Cells were grown in LB medium with 100 μg/ml ampicillin, 12 μg/ml chloramphenicol, and 6 mg/ml Fe(NH4)3 citrate under semi-anaerobic conditions (39Ubbink M. Van Beeumen J. Canters G.W. J. Bacteriol. 1992; 174: 3707-3714Crossref PubMed Google Scholar) at 35.5 °C, 150 rpm for 32 h up to an A600 of 1.3. Protein yields up to 1.5 mg/liter were obtained in this manner. The purification procedure used for Cf expressed from pEAF-WT will be described elsewhere. 2C. Albarrán, J. A. Navarro, F. P. Molina-Heredia, P. del S. Murdoch, M. A. De la Rosa, and M. Hervás, submitted for publication. NMR Sample Preparation—Pc and PCd protein solutions were concentrated to the required volume by ultrafiltration methods (Amicon, YM3 membrane) and exchanged into 10 mm sodium phosphate, pH 6.0, H2O/D2O 95:5 solutions. Protein concentrations were determined by absorption spectrophotometry using a ϵ598 of 4.5 mm–1 cm–1 for the oxidized form of Pc and a ϵ278 of 5.5 mm–1 cm–1 for PCd. The PCd ϵ278 was estimated using protein concentration values from Bradford assays. A A278/A598 ratio of 1.0 of the oxidized Pc indicated sufficient purity for characterization by NMR. The stock concentrations were 2.0 mm15N-labeled Pc and 2.7 mm15N-labeled PCd. The soluble domain of Cf was concentrated using Amicon YM10 membrane and exchanged into 10 mm sodium phosphate, pH 6.0, 3 mm sodium ascorbate, H2O/D2O 95:5 solutions. The concentration determination was based on optical spectroscopy using an ϵ556 of 31.5 mm–1 cm–1 for the reduced Cf (30Ubbink M. Ejdebäck M. Karlsson B.G. Bendall D.S. Structure. 1998; 6: 323-335Abstract Full Text Full Text PDF PubMed Scopus (259) Google Scholar). A 3.7 mm ferrous Cf stock solution with a A278/A598 ratio of 0.9 was used. Cf was kept in a reduced form with a few equivalents of sodium ascorbate and was stable in this form for days. The ferric form was prepared by the addition of a 5-fold excess of potassium ferricyanide (K3[Fe(CN)6]) followed by gel filtration (Amersham Biosciences Superdex G75) to remove ferrocyanide. Complete oxidation was verified by the disappearance of the absorption band at 556 nm. Then, a 2.0 mm ferric Cf stock solution was prepared. NMR Spectroscopy—All NMR experiments were performed on a Bruker DMX 600 NMR spectrometer operating at 298 K. The 1H and 15N assignments of reduced Nostoc Pc assignments were taken from Badsberg et al. (40Badsberg U. Jorgensen A.M. Gesmar H. Led J.J. Hammerstad J.M. Jespersen L.L. Ulstrup J. Biochemistry. 1996; 35: 7021-7031Crossref PubMed Scopus (73) Google Scholar). For sequence-specific assignment of the backbone amide resonances of PCd (Supplemental Table S2), a two-dimensional 1H,15N HSQC (41Andersson P. Gsell B. Wipf B. Senn H. Otting G. J. Biomol. NMR. 1998; 11: 279-288Crossref PubMed Scopus (23) Google Scholar), two-dimensional 1H,15N HSQC nuclear Overhauser enhancement spectroscopy with 150 ms mixing time, and two-dimensional 1H,15N HSQC total correlation spectroscopy with 80-ms mixing time spectra were recorded. The effects of complex formation on PCd were followed by acquiring two-dimensional 1H,15N HSQC spectra during titrations of aliquots of a 3.7 mm ferrous or 2.0 mm ferric Cf solution into a solution of 0.2 mm 15N-labeled PCd. The spectral widths were 32.0 ppm (15N) and 12.0 ppm (1H), and 256 and 1024 complex points were acquired in the indirect and direct dimensions, respectively. For measurements of the pseudo-contact shifts (PCS) 1H,15N HSQC spectra of free Pc, the oxidized complex and the reduced complex were acquired, always on the same sample. Ferric Cf from a stock solution was added to a 15N-labeled PCd sample with final concentrations of 0.35 and 0.50 mm, respectively. Cf was reduced with 10 mol eq of a concentrated sodium ascorbate solution. Given the final Cf concentration and the binding constant, the percentage of Pc bound was calculated to be 55%. All data processing was performed with AZARA (www.bio.cam.ac.uk/azara), and analysis of the chemical-shift perturbations (ΔδBind) with respect to the free protein was performed in Ansig (42Kraulis P.J. J. Magn. Reson. 1989; 84: 627-633Google Scholar, 43Kraulis P.J. Domaille P.J. Campbell-Burk S.L. van Aken T. Laue E.D. Biochemistry. 1994; 33: 3515-3531Crossref PubMed Scopus (289) Google Scholar, 44Helgstrand M. Kraulis P. Allard P. Hard T. J. Biomol. NMR. 2000; 18: 329-336Crossref PubMed Scopus (88) Google Scholar). The spectra were calibrated against the internal standard [15N]acetamide (0.5 mm). Binding Curves—Titration curves were obtained by plotting ΔδBind against the molar ratio of CfII/III:PCd for the most strongly affected signals. Non-linear least squares fits to a 1:1 binding model (21Kannt A. Young S. Bendall D.S. Biochim. Biophys. Acta. 1996; 1277: 115-126Crossref PubMed Scopus (118) Google Scholar) were performed in Origin 6.0 (Microcal Inc.). This model accounts for the dilution effect of both proteins during the titration, with the ratio of Cf and PCd and ΔδBind as the independent and dependent variables, respectively. The binding constant (Ka) and the maximum chemical shift change (Δδmax) were the fitted parameters. A global fit of the data was performed in which the curves were fitted simultaneously to a single Ka value, whereas the Δδmax for each resonance was allowed to vary. Chemical Shift Mapping—The shifts observed in the complex PCd-CfII with 3 eq of Cf were extrapolated to 100% bound for all residues using the Ka obtained from the fits. The average chemical-shift perturbation (Δδavg) of each amide was calculated using the following equation (45Grzesiek S. Bax A. Clore G.M. Gronenborn A.M. Hu J.S. Kaufman J. Palmer I. Stahl S.J. Wingfield P.T. Nat. Struct. Biol. 1996; 3: 340-345Crossref PubMed Scopus (306) Google Scholar),Δδavg=(ΔδN/5)2+ΔδH22eq.1 in which ΔδN is the change in the 15N chemical shift, and ΔδN is the change in the 1H chemical shift when the protein is 100% bound to Cf. Restraints Classes—Details of the restraints definitions are provided in the Supplemental Material. Briefly, four groups of restraints were defined. The interface restraints represent the chemical-shift perturbation data for Pc nuclei (Supplemental Table S1). These are satisfied when the nuclei are close the Cf surface. Additional interface restraints were defined to serve as a weak van der Waals repel function. PCS were used to define pseudo-contact restraints and angle restraints according to the procedure described in Ubbink et al. (30Ubbink M. Ejdebäck M. Karlsson B.G. Bendall D.S. Structure. 1998; 6: 323-335Abstract Full Text Full Text PDF PubMed Scopus (259) Google Scholar), and minimal distance restraints were defined for amide groups that did not experience a PCS. Electrostatic restraints based on kinetic rather than NMR data were used previously (30Ubbink M. Ejdebäck M. Karlsson B.G. Bendall D.S. Structure. 1998; 6: 323-335Abstract Full Text Full Text PDF PubMed Scopus (259) Google Scholar) to represent the electrostatic attraction between PCd and Cf. In the Nostoc complex, these were not used because the NMR experimental data were sufficient to obtain a well defined structure. A summary of the restraint groups is listed in Table I. The product between the number of restraints and the scaling factor used in the calculations indicates the importance of each restraint group. Note that the pseudo-contact restraints, which give quantitative information, are dominant.Table IRestraints groupsRestraint groupTypeNumber of restraintsScalingNumber × scalingInterfaceDistance415205Pseudo-contactDistance81201620Minimal distanceDistance9010900AngleAngle81aScaling of the angle restraints is not comparable with that of distance restraints.a Scaling of the angle restraints is not comparable with that of distance restraints. Open table in a new tab Nostoc Cf Homology Model—A homology model of Cf was built using the COMPOSER (46Blundell T. Carney D. Gardner S. Hayes F. Howlin B. Hubbard T. Overlington J. Singh D.A. Sibanda B.L. Sutclife M. Eur. J. Biochem. 1988; 172: 513-520Crossref PubMed Scopus (250) Google Scholar) module of SYBYL 6.5 (Tripos Inc.) using X-ray diffraction data from Brassica rapa, PDB entry 1CTM (resolution 2.30 Å (5Martinez S.E. Huang D. Szczepaniak A. Cramer W.A. Smith J.L. Structure. 1994; 2: 95-105Abstract Full Text Full Text PDF PubMed Scopus (261) Google Scholar)) and PDB entry 1HCZ (resolution 1.96 Å (47Martinez S.E. Huang D. Ponomarev M. Cramer W.A. Smith J.L. Protein Sci. 1996; 5: 1081-1092Crossref PubMed Scopus (132) Google Scholar)) as templates. Including the structure of Phormidium Cf (PDB entry 1CI3 (48Carrell C.J. Scharlb B.G. Bendall D.S. Howe C.J. Cramer W.A. Smith J.L. Biochemistry. 1999; 38: 9590-9599Crossref PubMed Scopus (72) Google Scholar)) as the template did not improve the model. Three sequence stretches (residues 1–9, 13–183, and 198–254) were considered as conserved. These regions showed identities of 66.7, 64.9, and 54.4%, respectively. Two loops corresponding to residues Trp-4—Gln-6 and Ala-184—Val-197 were simulated to allocate 1- and 3-residue insertions, respectively, using the TWEAK option. On average, the r.m.s.d. of backbone atoms of the model of Cf with respect to the above structures was 0.56 Å. The structure of Cf from Mastigocladus (made available only after completion of our calculations, PDB entry 1VF5 (6Kurisu G. Zhang H.M. Smith J.L. Cramer W.A. Science. 2003; 302: 1009-1014Crossref PubMed Scopus (598) Google Scholar)) shows a similar extension of the small domain of Cf. The Nostoc Cf model shows a 1.16-Å r.m.s.d. with this structure. The largest differences correspond to residues 184–197, which show high B-factors in the Mastigocladus Cf crystal structure, suggesting that this loop may be flexible. Structure Calculations—Structure calculations were performed using XPLOR-NIH Version 2.9.1 (49Brunger A.T. X-PLOR 3.1 Manual. Yale University Press, New Haven, Connecticut1992Google Scholar, 50Schwieters C.D. Kuszewski J.J. Tjandra N. Clore G.M. J. Magn. Reson. 2003; 160: 66-74Crossref Scopus (1870) Google Scholar). The structures of Nostoc Pc (PDB entry 1NIN (40Badsberg U. Jorgensen A.M. Gesmar H. Led J.J. Hammerstad J.M. Jespersen L.L. Ulstrup J. Biochemistry. 1996; 35: 7021-7031Crossref PubMed Scopus (73) Google Scholar)) and the homology model of Cf were treated as rigid bodies, and the co-ordinates of Cf were fixed. PCd was placed at a random position and allowed to move in a restrained rigid-body molecular dynamics calculation. None of the standard energy terms was used. Only the groups of experimental restraints described above were applied to dock the proteins. Five thousand cycles (see Supplemental Material) of calculations were performed (9 h on a dual processor Pentium IV PC running under LINUX). Only structures with a total restraints "energy" (Etot) below a threshold were saved, yielding ∼90 structures. To assure sufficient sampling of the orientation space, a large random displacement of Pc occurred when a (local) minimum had been found, as judged from a total restrained energy that had not changed for more than 50% during 10 cycles. About 200 of such displacements occurred in a representative run. As an illustration, Etot has been plotted against the cycle number in Fig. S2 for a sector of one trajectory, corresponding to 200 cycles. The resulting structures were ranked according to total restraint energy and the top ten structures, with total restraint energy values from 28 to 29 arbitrary units subjected to restrained energy minimization of the side chains followed by a short restrained rigid body energy minimization, both using the XPLOR-NIH repulsive van der Waals term with reduced scaling. This largely removed the collisions between Pc and Cf atoms while maintaining the low total restraint energy value. The ten best structures have been deposited in the Protein Data Bank under entry 1TU2. Buried surface areas have been calculated using NACESS (51Hubbard S.J. Campbell S.F. Thornton J.M. J. Mol. Biol. 1991; 220: 507-530Crossref PubMed Scopus (344) Google Scholar). Electron Transfer Pathways—To determine the residues that could be involved in the electron transport, the best electron transfer pathway for each of the energy-minimized complex structures was calculated using Greenpath Version 0.971 (52.Regan, J. J. (1994) Greenpath software, Version 0.9771, San Diego, CAGoogle Scholar). This program performs a Green function analysis based on two-state super-exchange model (53Skourtis S.S. Onuchic J.N. Chem. Phys. Lett. 1993; 209: 171-177Crossref Scopus (46) Google Scholar). No enhanced coupling was used for aromatic rings. For representation purposes, we selected all the coordinates of the residues that appear in any of these paths instead of just representing the bonds and jumps involved. Binding Affinity—To characterize the complex of Pc and Cf from Nostoc, Cf was titrated into a solution of 15N-labeled Cd-substituted Pc, PCd. The copper in Pc was replaced by the redox inactive substitute cadmium to allow for studies with both oxidized and reduced Cf without interference from electron transfer reactions. The effects of the titrations were followed with two-dimensional HSQC experiments. Shifting of resonances during the titration indicated that binding and dissociation were fast on the NMR timescale (>100 s–1). In Fig. 1, the chemical-shift perturbations due to binding to reduced Cf (CfII) are plotted for several residues of PCd. The curves clearly illustrate that the chemical-shift perturbations increase as a function of the CfII concentration. A global fit of the data to a 1:1 binding model (21Kannt A. Young S. Bendall D.S. Biochim. Biophys. Acta. 1996; 1277: 115-126Crossref PubMed Scopus (118) Google Scholar) yielded a binding constant of 16 ± 1 × 103m–1, and the same affinity was obtained with oxidized Cf (KA = 16 ± 2 × 103m–1; data not shown). This value is slightly lower than that obtained for native (Cu(I)) Nostoc Pc (26 ± 1 ×103m–1 (64Díaz-Moreno I. Díaz-Quintana A. De la Rosa M.A. Crowley P.B. Ubbink M. Biochemistry. 2005; 44: 3176-3183Crossref PubMed Scopus (34) Google Scholar)). Hence, it can be concluded that the binding affinity is independent of the oxidation state of Cf but appears to vary slightly between Pc with a singly charged metal and a doubly charged one. Interface Map—In Fig. 2, the size of the chemical-shift perturbations for residues affected upon titration with CfII are color-coded onto the surface of Pc. Perturbed residues map in sequence stretches 7–17, 32–44, 63–72, and 88–100. These stretches form a large area comprising residues from both classical binding sites (10Coleman P.M. Guss J.M. Sugimura Y. Yoshizaki F.Y. Freeman H.C. J. Mol. Biol. 1978; 211: 617-632Google Scholar, 25Lee B.H. Hibino T. Takabe T. Weisbeek P.J. Takabe T. J. Biochem. 1995; 117: 1209-1217Crossref PubMed Scopus (1) Google Scholar). Three proline residues, at positions 37, 38, and 91 (gray), are located in the middle of the interface, close to the copper ligand His-92. In addition to the main interaction area, three isolated residues (Lys-51, Asp-54, and Leu-55) undergo a significant perturbation. These residues are located in a region below site 2, comprising mainly charged residues that have an important role in the Nostoc complex structure, as is explained below. The perturbation map of PCd is similar to that found for Pc(Cu(I)) (64Díaz-Moreno I. Díaz-Quintana A. De la Rosa M.A. Crowley P.B. Ubbink M. Biochemistry. 2005; 44: 3176-3183Crossref PubMed Scopus (34) Google Scholar). The overall sizes of the perturbations and the localized nature of the binding map indicate that the complex between PCd and Cf is well defined according to the classification for well defined versus dynamic complexes, suggested by Worrall et al. (55Worrall J.A.R. Liu Y.J. Crowley P.B. Nocek J.M. Hoffman B.M. Ubbink M. Biochemistry. 2002; 41: 11721-11730Crossref PubMed Scopus (80) Google Scholar) and Prudêncio and Ubbink (56Prudêncio M. Ubbink M. J. M